Analisis SEM-PLS Perilaku Pasien HIV/AIDS terhadap Gambaran Klinis Pasien - Hiariey, Arlene Henny; Upuy, Doms; Latupeirissa, Sanlly Joanne (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2022)
Structural Equation Modeling (SEM) is a method of multivariate statistical analysis that can describes the structure of a relatively complex relationships by engaging many of the variables. SEM-based on component or a variant called Partial Least Square (PLS), is a method that is more flexible and powerful in testing with free distribution assumptions, the scale of the indicator variety, and the number of samples must not be large. Specific problems in the case of HIV/AIDS can be seen through clinical overview sufferers HIV/AIDS, based on opportunistic infections CD4 levels, and quality of life. This research aims to get Structural Equation Model (SEM-PLS) clinical picture of HIV/AIDS patients. Secondary data were gathered and derived from the medical records of 150 patients with HIV/AIDS at the health centers of the Pasuruan Regency in 2017. The results of the analysis showed that the predisposing factors, enabling factors and strengthening factors influenced the clinical picture of HIV/AIDS patients. R2 produced by 0,8 so it can be conclude that model can explain data.